Penguraian Rumput Laut Ulva Lactuca Untuk Mengukur Kadar Asam Amino dan Mengetahui Rendemen Polisacharida Menggunakan Kapang Laut EN - Putri, Ryana Tammi (Jurnal Agricultural Biosystem Engineering, 2025)
Ulva lactuca is classified as green alga which spreads out in sea water area in Indonesian especially Sulawesi, Lombok, Banda, Solor, Sumba, Jawa Barat, Lampung Selatan. They are commonly used as food ingredient or as biofilter. Ulva lactuca contains protein compound between 10-25% dry weight. Protein hydrolysis process was done to increase amino acid availability. EN fungi has been used to hydrolyze in this study. It was done for 2 days by magnetic stirrer at ambient temperature. Observed parameters during hydrolysis process were amino acid content, pH level, and polysaccharide content. The highest amino acid content was achieved at 12 hours of hydrolysis time with absorbance value at ±0.8840. The pH during hydrolysis was between 5-6. Polysaccharide content is analysis by precipitation with isopropyl alcohol. Amino acid profile is analysis by UPLC. The amino acid profile indicating that serine, glutamate acid, and glycine had high value at 366.66 ppm, 289.91 ppm, and 261.37 ppm, respectively. Triterpenoid and saponin compound has been detected. Keywords: Amino Acid, EN Fungi, Hydrolysis, Ulvan.